Can United States Healthcare Become Environmentally Sustainable? Towards Green Healthcare Reform. Issue 4 (December 2020) - Richie, Cristina
In 2014, the United States health care industry produced an estimated 480 million metric tons of carbon dioxide (CO2); nearly 8% of the country's total emissions. The importance of sustainability in health care — as a business reliant on fossil fuels for transportation, energy, and operational functioning — is slowly being recognized. These efforts to green health care are incomplete, since they only focus on health care structures. The therapeutic relationship is the essence of health care — not the buildings that contain the practice. As such, this article will first postulate reasons for a lack of environmental sustainability in US health care. Second, the article will focus on current green health care initiatives in the United States in which patients and physicians participate. Third, the rationale for participation in green initiatives will be explained. Fourth, the article will propose that, based on the environmental values of patients and physicians, health care insurance plans and health care insurance companies can be targeted for green health care reform, thereby closing the loop of sustainable health care delivery.